Oral health condition in a 6.5-year-old girl with Prader-Willie syndrome – case report - Błaszczak, Jerzy; MAŚLANKO, MONIKA; OLSZEWSKA, KATARZYNA; SKAWIŃSKA- BEDNARCZYK, AGNIESZKA; PIETRAK, JUSTYNA; Mielnik-Błaszczak, Maria (Journal of Stomatology, 2017)
Introduction: The Prader-Willi syndrome is associated with an abnormality occurring within chromosome pairs (15q11-13). During the neonatal period, PWS children are characterized by genital hypoplasia and muscle hypotension. Hyperphagia manifests itself in the pre-school period. The characteristic features of PWS also include low growth, small hands, mental retardation, and rebellious behavior. The aim of the study: Characteristic of case of 6,5 years old patient with PWS. Case report: A medical history was collected and subject-matter research was performed: extraoral and intraoral. Photo documentation was made. The patient was 112 cm tall and weighed 23.7 kg. The child's speech is unclear, but understandable. Up to 6 years of age, no hyperphagia or excessive anger have been observed in patients, but in recent months these issues have become more prominent. At age 3, she was treated twice under general anesthesia. All milk teeth are affected by caries, treated or removed for that reason. There are no caries or hypoplastic lesions on the surface of permanent teeth. Conclusions: 1. Due to such features as dense saliva, hyperphagia, acromicria, and behavioral and emotional factors PWS patients are particularly prone to developing stomatognathic diseases. 2. Patients with PWS and their careers should be encouraged to take preventive actions at home and in dental office. 3. The early loss of milk teeth and certain facial dysmorphic features make PWS patients often require orthodontic treatment.